Proceso de atención de enfermería en adulto joven con tumor maxilo-mandibular. - Bustamante Guadalupe, Ishel Karolina (2024)
The following case study is applied to a 19-year-old female patient who presented with a clinical picture of ±4 months of evolution characterized by a 12-centimeter circular mass in the mandibular region of a purplish color with redness and indura, plus a sensation of paresthesia in the the mandibular region that causes difficulty when ingesting solids plus pain on palpation. When vital signs were taken, the patient presented blood pressure: 100/65mmHg, heart rate: 70lxmin, respiratory rate: 19rxmin, oxygen saturation: 98%, temperature 38.5ºC. In the physical evaluation, a circular mass was observed in the mandible with redness and warmth to the touch, while the inner surface of the lower jaw was swollen. A peripheral line is placed in the left upper limb and a hydration plan, antibiotics, antipyretics and analgesics are administered. The doctor observes and orders a complete blood count, ultrasound in the mandibular region, X-ray of the face and skull plus Waters X-ray. The nursing assessment is carried out using Marjorie Gordon's functional patterns in order to identify the altered patterns and treat them immediately by applying the Nursing Care Process that will be provided during hospitalization and thus meet the objectives proposed in this study. clinical case.